Harvesting adaptation to biodiversity conservation in sawmill industry: technology innovation and monitoring program - Martínez Pastur, Guillermo José (2007)
Social demands related to native forest ecosystems are based on an efficient management, with a balance between conservation and timber production. This paper describes the industry adaptation to a biodiversity program with an alternative regeneration method. The proposed method leaves 30% of the timber-quality forest as aggregated retention and 15 m² ha-1 basal area as dispersed retention. While many costs increased considerably, the incomes also may increase by applying new management strategies and technology innovation. A monitoring program was established in the harvested stands to evaluate the ecological functionality of the applied regeneration system (forest structure, climate change, regeneration dynamics, habitat quality and abiotic cycles). The implementation of an innovated technology and monitoring program in the forest and industry determined a balance between economic values and biodiversity conservation.